Virtual Reality and Neurofeedback for Management of Cancer Symptoms: A Feasibility Pilot. (March 2023) - Rolbiecki, Abigail J.; Craig, Kevin; Megan Polniak,; Smith, Jamie; Ghosh, Parijat; Mehr, David R.
Background : Evidence suggests the usefulness of complementary and alternative medicine approaches, like neurofeedback and virtual reality, for the management of cancer-related pain and mood. It is not well-understood whether neurofeedback delivered through virtual reality is feasible and acceptable to patients actively undergoing cancer treatment.Objective : The purpose of this study was to explore the feasibility and acceptability of a nature-based virtual reality combined with neurofeedback as a non-pharmacologic strategy for managing cancer-related pain and anxiety.Methods : This study utilized a mixed-methods approach. Participants included 15 cancer patients undergoing treatment. Patients engaged in a 22-minute nature-based virtual reality experience, wearing a virtual reality headset with a Brainlink headband measuring EEG activity. Participants were asked to complete the Edmonton Symptom Assessment System revised version (ESAS-r) before (T1) and after (T3) the experience to measure pain and anxiety. They were asked their level of pain midway through the experience (T2) and completed a follow-up interview afterward.Results : This study revealed feasible delivery of a virtual reality intervention combined with neurofeedback for patients seeking cancer treatment. All participants (100%) completed the intervention experience. Patients report this is an acceptable approach to managing cancer-related pain and anxiety. Comparisons between patients' pain scores at T1, T2, and T3 reveal statistically significant reductions in pain (p .001). Patients also report decreased depression and anxiety.Conclusion : This is the first study examining virtual reality combined with neurofeedback as a non-pharmacologic intervention for managing cancer symptoms during treatment. The study reveals it is a promising for managing cancer-symptoms.